Prediction of optimal mechanical properties for a scaffold used in osteochondral defect repair - KELLY, DANIEL; Prendergast, Patrick John (Mary Ann Liebert, 2006)
The optimal mechanical properties of a scaffold to promote cartilage generation in osteochondral defects in vivo are not known. During normal daily activities cartilage is subjected to large cyclic loads that not only facilitate nutrient transport and waste removal through the dense tissue but also act as a stimulus to the chondrocytes. In contrast, cartilage tissue is commonly engineered in vitro in a static culture and hence, in many cases, the properties of scaffolds have been tailored to suit this in vitro environment. In this study, a mechano-regulation algorithm for tissue differentiation has been used to determine the influence scaffold material properties on chondrogenesis in a finite element model of an osteochondral defect. It is predicted that increasing the stiffness of the scaffold increases the amount of cartilage formation and reduces the amount of fibrous tissue formation in the defect, but this only holds true up to a certain threshold stiffness above which the amount of cartilage formed is reduced. Reducing the permeability of the scaffold was also predicted to be beneficial. Considering a nonhomogenous scaffold, an optimal design was determined by parametrically varying the mechanical properties of the scaffold through its depth. The Young?s modulus reduced non-linearly from the superficial region through the depth of the scaffold, while the permeability of the scaffold was lowest in the superficial region. As tissue engineering moves from a science towards a product, engineering design becomes more relevant, and predictive models such as that presented here can provide a scientific basis for design choices.
PUBLISHED
Keywords: Mesenchymal Stem Cells; Fundamentals of Tissue Engineering